2021
DOI: 10.1111/ijag.16322
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties in Tm3+/Tm3+–Yb3+ doped NaLuF4 glass‐ceramics

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The UC emission spectra are composed of two visible emission bands arising from the Tm 3+ transitions 1 G 4 → 3 H 6 (475 nm) and 1 G 4 → 3 F 4 (651 nm), the strong emission at 800 nm is attributed to the 3 H 4 → 3 H 6 transition in the first biological window. The DS emission spectra in the third biological window at 1625 nm is attributed to the transition 3 F 4 → 3 H 6 28 so they are especially appealing from a biological point of view. The NGVO:Tm 3+ ,Yb 3+ exhibit a stronger NIR emission at low excitation density, which has potential uses in deep tissue imaging, optical signal amplification and other fields.…”
Section: Resultsmentioning
confidence: 99%
“…The UC emission spectra are composed of two visible emission bands arising from the Tm 3+ transitions 1 G 4 → 3 H 6 (475 nm) and 1 G 4 → 3 F 4 (651 nm), the strong emission at 800 nm is attributed to the 3 H 4 → 3 H 6 transition in the first biological window. The DS emission spectra in the third biological window at 1625 nm is attributed to the transition 3 F 4 → 3 H 6 28 so they are especially appealing from a biological point of view. The NGVO:Tm 3+ ,Yb 3+ exhibit a stronger NIR emission at low excitation density, which has potential uses in deep tissue imaging, optical signal amplification and other fields.…”
Section: Resultsmentioning
confidence: 99%
“…A similar amount of fluorine loss was reported in other oxyfluoride silicate glasses. 11,26 Due to the high melting temperatures involved (1650 • C), such substantial fluorine losses are common in these compositions.…”
Section: Chemical and Thermal Analysesmentioning
confidence: 99%
“…They possess numerous energy levels that span a broad spectroscopic range, extending from the ultraviolet to near-infrared. In addition, Yb 3+ is frequently chosen as the sensitizer codoped with active lanthanide ions due to its two energy levels, which result in a greater absorption cross section at 975 nm and an efficient transfer of energy to adjacent lanthanide ions. Recently, an Er 3+ /Tm 3+ /Yb 3+ -tridoped system has attracted great interest for optical temperature sensing and white light UC emission. For example, Passuello et al reported a nanocrystalline gadolinium oxyfluoride sample doped with Er 3+ , Tm 3+ , and Yb 3+ for white light UC emission .…”
Section: Introductionmentioning
confidence: 99%